MERRF-Like Phenotype Associated with a Rare Mitochondrial tRNAIle Mutation (m.4284 G>A) - Hahn, A.; Schänzer, A.; Neubauer, B.A.; Gizewski, E.; Ahting, U.; Rolinski, B. (Neuropediatrics, 2011)
Nearly all patients affected by myoclonic epilepsy with ragged-red fibres (MERRF) harbour a mutation in the mitochondrial transfer RNALys gene. We report on an 8-year-old girl with clinical and diagnostic features of MERRF. After excluding one of the common mutations associated with MERRF, a complete sequence analysis of the mitochondrial genome revealed an m.4284 G>A mutation in the mitochondrial transfer RNAIle gene. This mutation has only once been described in a family with variable clinical symptoms, but has not yet been linked to MERRF. This case extends the mutational spectrum associated with the MERRF phenotype, and demonstrates the importance of performing a comprehensive mutational analysis in patients with suspected mitochondrial disease when common mutations have been ruled out.
Keywords: mitochondrial disorder; ragged-red fibres; progressive myoclonic epilepsy; MERRF; mtDNA-mutation